Pengaruh Harga dan Fasilitas Terhadap Kepuasan Pengunjung di Daya Tarik Wisata Bukit Chinangkiak Kabupaten Solok - Hafizah Febiola; Hijriyantomi Suyuthie (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study was to determine the effect of price and facilities on visitor satisfaction at the Bukit Chinangkiak tourist attraction in Solok Regency. This type of research is descriptive quantitative with survey method. The population is all tourists visiting the Bukit Chinangkiak tourist attraction and the total average number of tourists in January-December 2022 was 12,202 visitors and a sample of 387 respondents was determined. Data were collected from questionnaires that had been tested for validity and reliability. Multiple linear regression tests were used to test the research hypothesis with the help of SPSS 26.00, obtaining the results, namely: (1) Price with sufficient category (64.9%), Facilities with good category (65.3%) and Visitor Satisfaction with sufficient category (64.3%). A significant value of 0.000 < 0.05 is given in the estimated F value of 303.587. This shows that X1 and X2 have a large impact on Y simultaneously, so this hypothesis is correct, then the regression coefficient values for X1 and X2 are 0.727 and 0.092 respectively, with a significant level of 0.007 < 0.05. This shows that for every 1 unit increase in price, 0.727 more people will decide to visit, and for every 1 unit increase in facilities, 0.092 more people will decide to come. Then, the Adjust R square value is 0.611 which shows that the X1 and X2 variables have a large influence of 61.1%.